CAG Repeat Number in the Androgen Receptor Gene and Prostate Cancer - Madjunkova, S; Eftimov, A; Georgiev, V; Petrovski, D; Dimovski, Aj; Plaseska-Karanfilska, D (Walter de Gruyter GmbH, 2012)
Prostate cancer (PC) is the second leading cause of cancer deaths in men. The effects of androgens on prostatic tissue are mediated by the androgen receptor (AR) gene. The 5' end of exon 1 of the AR gene includes a polymorphic CAG triplet repeat that numbers between 10 to 36 in the normal population. The length of the CAG repeats is inversely related to the transactivation function of the AR gene. There is controversy over association between short CAG repeat numbers in the AR gene and PC. This retrospective case-control study evaluates the possible effect of short CAG repeats on the AR gene in prostate cancer risk in Macedonian males. A total of 392 male subjects, 134 PC patients, 106 patients with benign prostatic hyperplasia (BPH) and 152 males from the general Macedonian population were enrolled in this study. The CAG repeat length was determined by fluorescent polymerase chain reaction (PCR) amplification of exon1 of the AR gene followed by capillary electrophoresis (CE) on a genetic analyzer. The mean repeat length in PC patients was 21.5 ± 2.65, in controls 22.28 ± 2.86 (p = 0.009) and in BPH patients 22.1 ± 2.52 (p = 0.038). Short CAG repeats (<19) were found in 21.64% of PC patients vs. 9.43% in BPH patients (p = 0.0154). We also found an association of low Gleason score (<7) with short CAG repeat (<19) in PC patients (p = 0.0306), and no association between the age at diagnosis of PC and BPH and CAG repeat length. These results suggest that reduced CAG repeat length may be associated with increased prostate cancer risk in Macedonian men.